An Indole-Based Fluorescent Chemosensor for Detecting Zn2+ in Aqueous Media and Zebrafish - Donghwan Choe; Haeri So; Soyoung Park; Hangyul Lee; Ju Byeong Chae; Jiwon Kim; Ki-Tae Kim; Cheal Kim (Sensors, 2021)
An indole-based fluorescent chemosensor IH-Sal was synthesized to detect Zn2+. IH-Sal displayed a marked fluorescence increment with Zn2+. The detection limit (0.41 μM) of IH-Sal for Zn2+ was greatly below that suggested by the World Health Organization. IH-Sal can quantify Zn2+ in real water samples. More significantly, IH-Sal could determine and depict the presence of Zn2+ in zebrafish. The detecting mechanism of IH-Sal toward Zn2+ was illustrated by fluorescence and UV–visible spectroscopy, DFT calculations, 1H NMR titration and ESI mass.